Climate Control of an Smart Greenhouse based on Android - Alpay, Ozlem; Erdem, Ebubekir (Ieee, 2018)
Smart systems are systems used by new technologies that facilitate human life. Smart greenhouses have an important place in smart agriculture application. In this study, the amount of energy and water consumed for controlling the climate parameters of a greenhouse has been predicted by using data from node packets placed in the greenhouse. Node packs are placed in star topology using wireless sensor network Climate parameters are greenhouse internal temperature, relative humidity and soil moisture. For this purpose, temperature and humidity sensors have been used Output data has been obtained by applying fuzzy logic method to received input data from sensors. The user remotely has controlled and monitored the greenhouse via the developed Android-based interface.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Greenhouse climate control; Fuzzy Logic; Smart Greenhouse; Internet of Things